Association of IL-21 polymorphisms (rs907715, rs2221903) with susceptibility to multiple autoimmune diseases: A meta-analysis. (March 2015) - Liu, Jie; Cen, Han; Ni, Jing; Zhang, Min; Li, Peng; Yang, Xiao-Ke; Leng, Rui-Xue; Pan, Hai-Feng; Ye, Dong-Qing
Abstract Objectives: Previous published data indicated that interleukin-21 (IL-21) gene polymorphisms were shown to associate with multiple autoimmune diseases (ADs), but the results remain inconclusive. The aim of this study was to perform a meta-analysis to assess the overall association between IL-21 gene polymorphisms (rs907715, rs2221903) and multiple ADs. Methods: All eligible case–control studies were searched in the PubMed and Embase database. A meta-analysis was conducted on the association between the IL-21 gene variants and ADs using: (1) allelic contrast, (2) homozygote contrast, (3) the recessive model, and (4) the dominant model. Results: A total of 12 relevant studies including 10 535 cases and 19 356 controls were enrolled in this meta-analysis. A significant association between IL-21 rs907715 gene polymorphism and AD was found under the allelic (OR: 1.102, 95% CI: 1.057–1.149, p = 0.000), homozygous (OR: 1.220, 95% CI: 1.089–1.368, p = 0.001), dominant (OR: 1.160, 95% CI: 1.027–1.309, p = 0.017), and recessive genetic model (OR: 1.119, 95% CI: 1.055–1.187, p = 0.000) among Caucasian populations. However, there was no significant association between IL-21 rs2221903 polymorphism and AD in different genetic models. Conclusions: Data from the present study suggest that the IL-21 rs907715 polymorphism might be associated with multiple ADs susceptibility in Caucasians. Especially, the allele G of intronic rs907715 in IL-21 confers increased risk of ADs.